Mumbai fables - Prakash, Gyan, 1952- (Princeton University Press, 2010)
"A place of spectacle and ruin, Mumbai exemplifies the cosmopolitan metropolis. It is not just a big city but also a soaring vision of modern urban life. Millions from India and beyond, of different ethnicities, languages, and religions, have washed up on its shores, bringing with them their desires and ambitions. Mumbai Fables explores the mythic inner life of this legendary city as seen by its inhabitants, journalists, planners, writers, artists, filmmakers, and political activists. In this remarkable cultural history of one of the world's most important urban centers, Gyan Prakash unearths the stories behind its fabulous history, viewing Mumbai through its turning points and kaleidoscopic ideas, comic book heroes, and famous scandals. Starting from the catastrophic floods and terrorist attacks of recent years, Prakash reaches back to the sixteenth-century Portuguese conquest to reveal the stories behind Mumbai's historic journey. Examining Mumbai's role as a symbol of opportunity and reinvention, he looks at its nineteenth-century development under British rule and its twentieth-century emergence as a fabled city on the sea. Different layers of urban experience come to light as he recounts the narratives of the Nanavati murder trial and the rise and fall of the tabloid Blitz, and Mumbai's transformation from the red city of trade unions and communists into the saffron city of Hindu nationalist Shiv Sena. Starry-eyed planners and elite visionaries, cynical leaders and violent politicians of the street, land sharks and underworld dons jostle with ordinary citizens and poor immigrants as the city copes with the dashed dreams of postcolonial urban life and lurches into the seductions of globalization. Shedding light on the city's past and present, Mumbai Fables offers an unparalleled look at this extraordinary metropolis"--Page [2-3] of dust jacket.